MOXIBUSTION HAS A POSITIVE EFFECT ON PULMONARY FIBROSIS: AN ALTERNATIVE APPROACH - Cheng, Lin; Li, Rong; Zhou, Mijuan; Li, Fuhong; Chang, Quanying; Li, Cuixia; Lu, Xuejing (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: An increasing number of people suffered idiopathic pulmonary fibrosis (IPF) and the current treatment was far from clinical satisfaction. Moxibustion, another effective and safe unconventional therapy, had been introduced to treat this refractory disease. The study aimed to investigate the effect of moxibustion on a bleomycin A5-induced pulmonary fibrosis model”. Please add a” before bleomycin A5. Please capital Eosin in Hematoxylin and Eosin (H.E.) staining. Materials and Methods: Sprague-dawley (SD) rats were randomly allocated to the blank group, model group, moxibustion group, and prednisone group, for which they received no treatment, modeling, moxibustion treatment and prednisone treatment. After four-week treatment, the rats were euthanized for Hematoxylin and Eosin (H.E.) staining, and TGF-β1 and IFN-γ protein and mRNA detection in lungs. Results: In the model group, TGF-β1 was significantly increased and IFN-γ was significantly decreased at both protein and mRNA levels in comparison to the blank group. In the moxibustion and prednisone groups, however, TGF-β1 was decreased and IFN-γ was increased at both protein and mRNA levels in comparison to the model group. Compared with prednisone, moxibustion showed comparable effect in lowing TGF-β1 (P>0.05) and better effect in up-regulating IFN-γ (P<0.05). Conclusion: The study concludes moxibustion protected pulmonary fibrosis by downregulating TGF-β1 and upregulating IFN-γ cytokines at both mRNA and protein levels, and the effect was comparable to prednisone. Moxibustion could be used as a therapeutic alternative treatment for pulmonary fibrosis.